The Development of Thinking Skills in English as a Second Language Methodology Classroom - Gembaruk, Alla (Educational Challenges, 2023)
This article focuses on an important aspect of modern education – the development of thinking skills. The purpose of this article is to outline the way thinking skills are developed in English as a Second Language (ESL) Methodology. The research was undertaken at Pavlo Tychyna Uman State Pedagogical University. The methodology is based on a review of academic literature, analyses of core Curriculum and ESL Methodology course books, and a generalization of our own ESL Methodology teaching experience. Results. The notion of thinking skills is revealed and their role for language learning is emphasized in the article. It is concluded that the development of thinking skills greatly depends on the quality of instruction, hence the requirement to enhance the ability of preservice teachers to develop thinking skills in their learners. To understand students’ readiness to develop thinking skills in their learners the PRESETT Curriculum on Methodology (Bachelor’s Level) and ESL Methodology coursebooks were thoroughly studied in terms of the aspects relevant to this research. The general overview of the core Curriculum in terms of the suggested modules, units and learning outcomes proved that the development of higher-order thinking skills is one of its main objectives. According to the core Curriculum thinking skills are developed through a range of teaching approaches, among them task-based learning, the use of case studies, simulations, group projects and problem solving. Such modes of teaching and learning promote high level interaction as well as the high level of thinking skills development. The analysis of the ESL Methodology coursebooks provides much more detailed overview of the activities practiced during the sessions, thus giving additional support for the research. It is proposed that competencies can be improved by means of HOT skills activities in the ESL Methodology classes. Conclusions. The research findings have enriched our understanding of thinking skills and highlighted the importance of their development in preservice teachers so that they are able to develop thinking skills in their future leaners. Taken together, the research results suggest that both thinking skills and life skills, such as communication, teamwork, critical thinking, problem-solving, information literacy, creativity, etc., are focused on in both the PRESETT Curriculum on Methodology and in the ESL Methodology coursebooks.